The Effect of Academic Supervision and Organizational Culture on Teacher Performance - Syahli Lastri1; Sudarno; Ajat Sudrajat (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Every educational institution has the same goal to improve the quality of education. Teacher performance is one of the important factors in efforts to improve the quality of education, which can be influenced by academic supervision and organizational culture. In fact, the existing problem in the schools so far is that teacher performance is still not optimal. There are still teachers who are incompetent in learning and there are still a number of teachers who cannot maximize their teaching. Hence, the study aims to determine and analyze the effect of academic supervision and organizational culture on teacher performance. The research method is field research with a quantitative approach. The research sample is public junior high school teachers who are civil servants at the Pasir Penyu District in Indragiri Hulu. The research instrument used is a questionnaire. Data collection techniques are observation, interview, and questionnaire. Data analysis techniques consist of quantitative and qualitative analyses. The research results reveal that academic supervision and organizational culture have a significant effect on teacher performance at public junior high schools in Pasir Penyu District with a positive effect direction. Thus, academic supervision and organizational culture factors support each other in maximizing teacher performance.